The Role of the NF-kB Pathway in Intracranial Aneurysms - Laurentiu Andrei Blaj; Andrei Ionut Cucu; Bogdan Ionel Tamba; Mihaela Dana Turliuc (Brain Sciences, 2023)
The pathophysiology of intracranial aneurysms (IA) has been proven to be closely linked to hemodynamic stress and inflammatory pathways, most notably the NF-kB pathway. Therefore, it is a potential target for therapeutic intervention. In the present review, we investigated alterations in the vascular smooth muscle cells (VSMCs), extracellular matrix, and endothelial cells by the mediators implicated in the NF-kB pathway that lead to the formation, growth, and rupture of IAs. We also present an overview of the NF-kB pathway, focusing on stimuli and transcriptional targets specific to IAs, as well as a summary of the current strategies for inhibiting NF-kB activation in IAs. Our report adds to previously reported data and future research directions for treating IAs using compounds that can suppress inflammation in the vascular wall.